Technology Adaptation in 21st Century Physical Education Learning: Literature Review - Ians Aprilo; Poppy Elisano Arfanda; M. Adam Mappaompo; M. Sahib Saleh; Hasbunallah (LPPM Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
The problem that arises is the use of technology in 21st-century physical education learning. Educators are required to use technology in every lesson that is carried out, to the demands and learning outcomes. The purpose of this paper is to present the advantages and disadvantages of technology in physical education learning based on the opinions of several previous studies. The writing of this article is a literature review in nature, analyzing reports that are relevant to the use of technology in learning. Literature was obtained using the search application on Google Scholar, Science Direct, Scopus, Web of Science, and books by entering the keywords